Aspectos epidemiológicos, perfil dos sorotipos e suscetibilidade antimicrobiana de cepas invasivas do Streptococcus pneumoniae em um hospital público - Paula, Alan de (2004)
The aim of this study was to evaluate, among invasive streptococcus pneumonia strains, the profile of serotypes and the implications for the formulation of pneumococcal vaccines, susceptibility to antimicrobials and also clinical and epidemiological aspects of patients with invasive pneumococcal disease. pneumococcal recovery. The strains isolated from the Clinical Analysis Laboratory of the Clinical Hospital of the Federal University of Uberlândia, MG, from clinical samples of patients with invasive disease, were identified and sent to the Adolfo Lutz Institute, São Paulo, SP, for confirmation of identification. serotyping and antimicrobial susceptibility determination. From April 1999 to March 2003, 148 invasive strains were isolated, 84 (56.7%) from male patients. The age ranged from one day to 88.8 years, with a mean of 21.3 ± 25.8 years and a median of 4.4 years. The most common clinical diagnoses were pneumonia [91 cases (61.4%)], meningitis [32 cases (21.6%)] and bacteremia without overt focus [15 cases (10.1%)]. The main sources of recovery were blood [76 samples (51.3%)], pleural fluid [39 (26.3%)] and cerebrospinal fluid [30 (20.2%)]. Death occurred in 22.3% of patients, with significantly higher numbers in those over 64 years. A total of 23 different serotypes were identified among 143 samples tested and the most common were 14, 1, 3, 5, 6A, 6B and 18C. Coverage figures for the currently available 7-valent vaccine were 46.7% of serotypes and 63.6% of strains obtained from children up to five years old. Of 30 (20.2%) oxacillin-resistant strains, 23 (15.5%) confirmed resistance to penicillin (12.8% at intermediate level and 2.7% at full level), which was restricted to serotypes 14, 23F, 19A and 6B, and predominated in individuals up to two years old (p = 0.0008). There was a high agreement of the penicillin minimum inhibitory concentration values ​​between the two methods employed. Decreased susceptibility to cotrimoxazole (63.4%), erythromycin (8.3%), clindamycin (8.7%) and ofloxacin (0.8%) were detected. Cefotaxime resistance was detected in three of the 30 strains tested (2% of 148), all with confirmed penicillin resistance. No resistance to chloramphenicol, rifampicin or vancomycin was observed.